Comparative transcriptomic analysis identifies KcMYB1 as a R2R3-MYB anthocyanin activator in Kadsura coccinea. (November 2022) - Huang, Ding; Xu, Shiqiang; Qin, Yanhong; Li, Yingjie; Ming, Ruhong; Huang, Rongshao; Wang, Jihua; Tan, Yong
Abstract: Fruit color, as an important appearance attribute, is crucial for attracting consumers. However, the underlying mechanism regulating mature fruit color formation in Kadsura coccinea remains unclear. Here, a comprehensive metabolomics and transcriptomics analysis was performed to investigate the molecular mechanisms of anthocyanin accumulation between two K. coccinea cultivars with different mature fruit colors—'Dahong No. 1′ (red) and 'Jinhu' (yellow). Targeted metabolomic analysis revealed high anthocyanin levels, most of which were cyanidin and delphinidin derivatives, in 'Dahong No. 1′ mature fruit peel. The SNP analysis indicated that the two different cultivars had similar genetic background. Moreover, comparative transcriptomic analysis demonstrated that differentially expressed genes (DEGs) were related to flavonoid biosynthesis and metabolic process in the two K. coccinea cultivars. Gene expression profiling data showed that the structural and regulatory genes associated with anthocyanin biosynthesis were significantly upregulated in 'Dahong No. 1′ mature fruit peel, which was verified by quantitative real-time polymerase chain reaction (qRT-PCR). Notably, the key anthocyanin activator KcMYB1 was identified, which was significantly upregulated in 'Dahong No. 1′ compared with 'Jinhu'. We further confirmed that KcMYB1 actively regulated the accumulation of anthocyanin by ectopic expression in vivo. Furthermore, allelic constitution of KcMYB1 in K. coccinea were investigated. The present study can provide insights for understanding the regulatory mechanisms of anthocyanin differential accumulation in the mature fruits of K. coccinea . Highlights: Targeted metabolomic analysis revealed composition of anthocyanin components in the fruits of Kadsura coccinea . Potentially structural and regulatory genes associated with anthocyanin biosynthesis were identified in Kadsura coccinea . Identification and characteristics of key anthocyanin activator KcMYB1 in Kadsura coccinea . Foundation for facilitating the improvement and breeding of Kadsura coccinea for fruit color.